A Crisis of Lordship: Robert Ogle, Fifth Lord Ogle, and the Rule of Early Tudor Northumberland*. (2nd January 2018) - Ellis, Steven G.
Abstract : Henry Tudor's diffusion of power in the English far north, and his savage pruning of resources for his wardens there to maintain good rule and defence, were perhaps necessary steps initially to prevent further challenges from overmighty subjects. Twenty years later, this was no longer an issue; and once peace with Scotland collapsed, the absence of the region's traditional ruling magnates was keenly felt. Under Henry VIII, an obscure border baron, Lord Ogle of Bothal, was often Northumberland's only resident lord, precipitating a crisis of lordship described as 'the decay of the borders'. Unable to recruit as warden a reliable magnate on acceptable terms, Henry VIII then decided that, as a matter of principle, he would 'not be bound, of a necessity, to be served there with lords'. The King appointed himself as warden-general, delegating the real work to gentlemen deputy wardens whose manraed was enhanced by feeing other leading local landowners, including Lord Ogle. Ogle's kin and connection thus supplied successive wardens with an adequate following in peacetime; but in the ensuing war Ogle was overwhelmed with his warden on Ancrum Moor, becoming the only nobleman in England under Henry VIII to die in battle.